Multi-omics study on biomarker and pathway discovery of chronic obstructive pulmonary disease. (1st September 2021) - Tang, Yuqing; Chen, Zhengjun; Fang, Zhiling; Zhao, Jinshun; Zhou, Yuping; Tang, Chunlan
Abstract: Chronic obstructive pulmonary disease (COPD) is a common heterogeneous respiratory disease characterized by persistent and incompletely reversible airflow limitation. Due to the heterogeneity and phenotype complexity of COPD, traditional diagnostic methods can only provide limited information on predicted results and treatment, which are not sufficient for accurate diagnosis and evaluation. With the development of omics technologies in recent years, genomics, proteomics and metabolomics are widely used in the study of COPD, providing good tools for discovering biomarkers to diagnose and elucidate the complex mechanism of COPD. In this review, we summarize the biomarkers of COPD based on metabolomic, proteomic and transcriptomic studies that have been reported in recent years. Furthermore, protein–protein interactions and multi-omics integrated analyses were carried out to explore the important metabolites and proteins that are involved in significant pathways in the progression of COPD in order to explain the pathogenesis of COPD. Finally, the prospects and challenges in the study of COPD are proposed. It is expected that this review will provide some references for the development of diagnostic methods and elucidation of the pathogenesis of COPD.